Analysis of Raw Material Inventory Control in The Amplang Production Process (Case Study: UD Taufik Jaya Makmur) - Mangkona, Fadhylah Anasia; Wahyuda, Wahyuda; Sitania, Farida Djumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
UD Taufik Jaya Makmur is an SME that produces amplang in various shapes and packaging sizes. Inventory control at this SME faces several issues, such as the lack of production scheduling, high inventory costs, and changes in raw material prices, especially for tapioca flour and fish. These problems impact the quality of service and provide opportunities for competitors to attract consumers. Therefore, a deterministic method is employed to achieve optimal inventory control, which includes methods such as Economic Order Quantity (EOQ), Period Order Quantity (POQ), Least Unit Cost (LUC), Least Total Cost (LTC), Economic Part Period ( EPP), Part Period Balancing (PPB), Silver Meal, and Wagner Within. Calculations indicate that the optimal inventory for tapioca flour, after considering the minimum purchase lot from suppliers and warehouse capacity, is achieved using the Economic Part Period (EPP), Part Period Balancing (PPB), and Wagner Within methods. The inventory cost for meeting the demand for the next year is IDR733.802, with savings reaching 72% compared to the business policy. For fish, the optimal inventory is achieved using the Period Order Quantity (POQ), Least Unit Cost (LUC), Least Total Cost (LTC), and Wagner Within methods. The inventory cost is IDR9.159.728, with savings reaching 37% compared to the business policy. Sensitivity analysis shows that inventory control for tapioca flour and fish is sensitive to ordering costs (distribution), necessitating recalculations if there are future changes.